Pertimbangan Hakim dalam Menjatuhkan Putusan Tindak Pidana Pengeroyokan: Analisis Hukum Positif dan Tujuan Hukum - muhammad irfansyah (Jurnal Hukum Lex Generalis, 2026)
This study analyzes judicial considerations in sentencing mob assault (pengeroyokan) offenses under Indonesian positive law. This study employs a normative legal research method with statutory and conceptual approaches. The results indicate that judicial considerations rely heavily on proving the elements of Article 466 of the Criminal Code (KUHP), valid evidence, and the perpetrator's guilt. However, differing interpretations of the element "collective force" (tenaga bersama) still persist, leading to consistency issues in court judgments. From the perspective of legal objectives, legal certainty has been achieved, whereas the aspects of justice and utility remain suboptimal. Therefore, the Supreme Court needs to formulate clearer implementation guidelines for mob assault offenses to enhance judgment consistency and achieve a balanced alignment among justice, legal certainty and utility.